Evaluation of the impact of the pay gap on performance - A study of dual system banking - S Martono; Fachrurrozie Fachrurrozie; Hasan Mukhibad; Ahmad Nurkhin; Kusumantoro Kusumantoro (Cogent Business & Management, 2022)
This study examines the effect of the pay gap on banks and compares the effectiveness of the tournament theory in Islamic banks (IB) and conventional banks (CB). This study expands the pay gap indicators used in previous studies by using three indicators: board of directors' pay gap, commissioners' pay gap and employees' pay gap. The sample is 23 banks, observed from 2009 to 2019, which results in 239 bank-years. The test results show that we have not found a relationship between a pay gap and bank performance. However, the subsample test, which involves separating Islamic banks and conventional banks, reports different findings. The tournament theory is effectively applied to the employee payroll system and shows a large employee pay gap will improve the performance of IBs and CBs. However, the effect of tournaments on IBs is greater than it is on CBs. The tournament theory is not effectively applied to the salary system for the boards of commissioners. However, the large pay gap for board of directors of CBs causes communication, coordination and collaboration problems between the board of directors and further reduces bank performance. However, in IBs, the pay gap of board of directors has no effect on bank performance. We recommend that banks should provide different salaries for employees at the various different levels. However, we do not recommend that banks create a large pay gap for board of directors because this will lead to poorer performance.
Keywords: 650; communication; coordination; Islamic bank; Pay gap; tournament theory